2000
DOI: 10.1002/(sici)1522-2675(20000119)83:1<93::aid-hlca93>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Tetrakis(phenylamidinium)-Substituted Resorcin[4]arene Receptors for the Complexation of Dicarboxylates and Phosphates in Protic Solvents

Abstract: Three bowl‐type cavitand receptors (1 – 3), consisting of a resorcin[4]arene core with four convergent phenylamidinium groups, were prepared in gram quantities by efficient synthetic routes (Schemes 1 and 2) for the recognition of organic anions in CD3OD and D2O. The key steps in the syntheses are the Suzuki cross‐coupling reactions between the tetraiodo cavitands 12, 13, and 23, respectively, with the m‐cyanophenylboronic ester 14 and subsequent conversion of the nitrile to amidinium groups by the Garigipati … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…1,2 Like guanidine, 32 amidine groups are superbases with pK a of ∼12 in water 33 and can form strong stoichiometric electrostatic interactions with carboxylates 34 and phosphates. 35 Recently, we have synthesized a benzamidine-based monomer ((4-acrylamidophenyl)(amino)methaniminium acetate (AB)) (Figure 3), which forms a 1:1 AB-carboxylate template complex with a high association constant (K a > 900 M −1 ), 34 in CD 3 OD/ D 2 O (4/1), as determined by 1 H NMR spectroscopy. 25,36 The resulting MIPs displayed high specificity and selectivity for their target molecules in aqueous conditions.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Like guanidine, 32 amidine groups are superbases with pK a of ∼12 in water 33 and can form strong stoichiometric electrostatic interactions with carboxylates 34 and phosphates. 35 Recently, we have synthesized a benzamidine-based monomer ((4-acrylamidophenyl)(amino)methaniminium acetate (AB)) (Figure 3), which forms a 1:1 AB-carboxylate template complex with a high association constant (K a > 900 M −1 ), 34 in CD 3 OD/ D 2 O (4/1), as determined by 1 H NMR spectroscopy. 25,36 The resulting MIPs displayed high specificity and selectivity for their target molecules in aqueous conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The tetra-cationic cavitand 84 4+ was used for the binding of carboxylate anions in water . Isophthalates, such as 85 2– (Figure ), formed 1:1 and 2:1 guest/host complexes with receptor 84 4+ in pure D 2 O ( K a ( 85 2– ⊂ 84 4+ ) = 8.6 × 10 4 M –1 and K a ( 85 2– ⊂ 84 4+ ⇌ [ 85 2 ] 4– ⊂ 84 4+ ) = 7.7 × 10 3 M –1 ).…”
Section: Covalent Receptors Possessing a Concave Hydrophobic Cavitymentioning
confidence: 99%
“…Diederich et al elaborated the aromatic cavity of the resorcin [4]arene scaffold by functionalizing the resorcinol units at their para-position with phenyl substituents, 230 84 (Figure 39). In addition, the authors used ethylene chains to bridge the resorcinol OHs of the receptor's scaffold.…”
Section: Resorcin[4]arenesmentioning
confidence: 99%
“…Benzamidinium groups have also proven useful in supramolecular chemistry, both in the context of host–guest chemistry and in self-assembly. Early studies by Nocera, Gale, , and Diederich , demonstrated that strong interactions were possible between the benzamidinium group and carboxylates in solution (including in polar organic solvents and water), and these and similar interactions have subsequently been used to prepare a range of self-assembled structures. Notably, Crego-Calama’s group pioneered the development of capsules based on benzamidinium···carboxylate and benzamidinium···sulfonate interactions, , and Yashima has developed a range of structures including catenanes, helices, and capsules assembled via benzamidinium···carboxylate hydrogen bonds. More recently, our group and the groups of Ben and Comotti , have demonstrated that benzamidinium groups can be used to form hydrogen bonded frameworks with carboxylate and sulfonate anions.…”
Section: Introductionmentioning
confidence: 99%